29 m6A-RNA Methylation (Epitranscriptomic) Regulators Are Regulated in 41 Diseases including Atherosclerosis and Tumors Potentially via ROS Regulation – 102 Transcriptomic Dataset Analyses. (15th February 2022) - Liu, Ming; Xu, Keman; Saaoud, Fatma; Shao, Ying; Zhang, Ruijing; Lu, Yifan; Sun, Yu; Drummer, Charles; Li, Li; Wu, Sheng; Kunapuli, Satya P.; Criner, Gerard J.; et al.
Abstract : We performed a database mining on 102 transcriptomic datasets for the expressions of 29 m 6 A-RNA methylation (epitranscriptomic) regulators (m 6 A-RMRs) in 41 diseases and cancers and made significant findings: (1) a few m 6 A-RMRs were upregulated; and most m 6 A-RMRs were downregulated in sepsis, acute respiratory distress syndrome, shock, and trauma; (2) half of 29 m 6 A-RMRs were downregulated in atherosclerosis; (3) inflammatory bowel disease and rheumatoid arthritis modulated m 6 A-RMRs more than lupus and psoriasis; (4) some organ failures shared eight upregulated m 6 A-RMRs; end-stage renal failure (ESRF) downregulated 85% of m 6 A-RMRs; (5) Middle-East respiratory syndrome coronavirus infections modulated m 6 A-RMRs the most among viral infections; (6) proinflammatory oxPAPC modulated m 6 A-RMRs more than DAMP stimulation including LPS and oxLDL; (7) upregulated m 6 A-RMRs were more than downregulated m 6 A-RMRs in cancer types; five types of cancers upregulated ≥10 m 6 A-RMRs; (8) proinflammatory M1 macrophages upregulated seven m 6 A-RMRs; (9) 86% of m 6 A-RMRs were differentially expressed in the six clusters of CD4 + Foxp3 + immunosuppressive Treg, and 8 out of 12 Treg signatures regulated m 6 A-RMRs; (10) immune checkpoint receptors TIM3, TIGIT, PD-L2, and CTLA4 modulated m 6 A-RMRs, and inhibition of CD40 upregulated m 6 A-RMRs; (11) cytokines and interferons modulated m 6 A-RMRs; (12) NF- κ B and JAK/STAT pathways upregulated more than downregulated m 6 A-RMRs whereas TP53, PTEN, and APC did the opposite; (13) methionine-homocysteine-methyl cycle enzyme Mthfd1 downregulated more than upregulated m 6 A-RMRs; (14) m 6 A writer RBM15 and one m 6 A eraser FTO, H3K4 methyltransferase MLL1, and DNA methyltransferase, DNMT1, regulated m 6 A-RMRs; and (15) 40 out of 165 ROS regulators were modulated by m 6 A eraser FTO and two m 6 A writers METTL3 and WTAP. Our findings shed new light on the functions of upregulated m 6 A-RMRs in 41 diseases and cancers, nine cellular and molecular mechanisms, novel therapeutic targets for inflammatory disorders, metabolic cardiovascular diseases, autoimmune diseases, organ failures, and cancers.